Evaluation of Left Atrial Function: Current Status. Issue 3 (4th July 2017) - Hoit, Brian D.
ABSTRACT: This review examines the current status of measuring left atrial mechanical functions and the ability of atrial functional analysis to predict cardiovascular outcomes. Increasing data support the use of echocardiography, computed tomography, and cardiac magnetic resonance in this regard. This review will discuss the various techniques used to assess left atrium reservoir, conduit, and booster pump functions and will focus on their ability to predict cardiovascular events in general and referral populations, and in patients with atrial fibrillation and other heart diseases.